Practical game design : learn the art of game design through applicable skills and cutting-edge insights - Kramarzewski, Adam; De Nucci, Ennio (Packt Publishing, 2018)
If you are looking for an up-to-date and highly applicable guide to game design, then you have come to the right place! Immerse yourself in the fundamentals of game design with this book, written by two highly experienced industry professionals to share their profound insights as well as give valuable advice on creating games across genres and development platforms.